Hubungan Obesitas Dengan Ketidakteraturan Siklus Menstruasi - Hapsari Nur Primastuti; Eriana Melinawati; Vicky Eko N.H (Nexus Biomedika, 2012)
Background : The purpose of this research was to know the relationship between obesity and irregularity menstrual cycle. Methods: This was an analytic observational study with cross sectional approach, using purposive sampling technique. The samples were 76 women, 20 35 years-old from Minomartani Village, Ngaglik, Sleman. Body Mass Index (BMI) data were obtained by measuring the height and weight, while the type of menstrual cyle by interview, on April 2012. Data were analyzed by Chi Square and Odds Ratio test. Results: Thirty women had BMI more than 25 kg/m2 (obese) and fourty six women had BMI between 18.5-24.9 kg/m2 (normal). The Chi Square test showed the value of p was 0.035 (p < 0.05), while the Odds Ratio test showed that value of OR was 3.154 (OR>1). Conclusions: There was significant relationship between obesity and irregularity menstrual cycle in fertile women in Minomartani village, Ngaglik, Sleman. Keywords: Obesity, Menstrual Cycle